2007
DOI: 10.1177/1084713807304357
|View full text |Cite
|
Sign up to set email alerts
|

Binaural-Bimodal Fitting or Bilateral Implantation for Managing Severe to Profound Deafness: A Review

Abstract: There are now many recipients of unilateral cochlear implants who have usable residual hearing in the non-implanted ear. To avoid auditory deprivation and to provide binaural hearing, a hearing aid or a second cochlear implant can be fitted to that ear. This article addresses the question of whether better binaural hearing can be achieved with binaural/bimodal fitting (combining a cochlear implant and a hearing aid in opposite ears) or bilateral implantation. In the first part of this article, the rationale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
224
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(251 citation statements)
references
References 111 publications
(129 reference statements)
22
224
4
1
Order By: Relevance
“…In addition, processing time differences between devices or the use of directional microphones on one or both devices may also be factors. For CI+HA users, digital processing delays (or 'group' delay; e.g., Dillon et al, 2003) and different compression and microphone characteristics (e.g., Ching et al, 2007;Musa-Shufani et al, 2006) can result in time delays and have the potential to negatively affect speech understanding and localization.…”
Section: Interaural Time Differencesmentioning
confidence: 99%
“…In addition, processing time differences between devices or the use of directional microphones on one or both devices may also be factors. For CI+HA users, digital processing delays (or 'group' delay; e.g., Dillon et al, 2003) and different compression and microphone characteristics (e.g., Ching et al, 2007;Musa-Shufani et al, 2006) can result in time delays and have the potential to negatively affect speech understanding and localization.…”
Section: Interaural Time Differencesmentioning
confidence: 99%
“…With clinical devices, it has been demonstrated that adding a hearing aid in the nonimplanted ear improves sound source localization and speech perception, as illustrated in a review by Ching et al (2007). However, with their clinical devices, most bimodal listeners are unable to use interaural timing cues which, for normal hearing (NH) listeners, are important for sound source localization and related to binaural unmasking of speech in the presence of spatially separated interfering sounds (Akeroyd 2006;Bronkhorst 2000;Colburn et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With clinical devices, it has been demonstrated that a contralateral hearing aid improves sound source localization and speech perception performance, as illustrated in a recent review by Ching et al (2007). While performance improves by adding a contralateral hearing aid (HA), it is still poor compared to NH listeners.…”
Section: Introductionmentioning
confidence: 99%